The Influence Of Communication And Work Discipline On Employee Performance - Dede Hertina; Sagit Sumpena; Risman Rismawan (Jurnal Manajemen Industri dan Logistik, 2022)
The purpose of this study is to test and analyze the influence of communication and work discipline on employee performance. Data collection is carried out by the dissemination of questionnaires, the population of this study is Bank BJB Sumbersari Bandung Branch Of which numbered 60 respondents using purposive sampling obtained a sample of 50 respondents. This research method uses a quantitative descriptive approach method. The results of the study showed that simultaneous communication and work discipline affect employee performance. This is evidenced by the results of the Simultaneous Test (test f) and partial test (test t). Therefore, the test results of this study stated that there is a simultaneous influence between communication variables and work discipline on the performance of employees of Bank BJB Sumbersari Bandung Branch